Repetitive Exposure of IL-17 Into the Murine Air Pouch Favors the Recruitment of Inflammatory Monocytes and the Release of IL-16 and TREM-1 in the Inflammatory Fluids - Maione, Francesco; Iqbal, Asif Jilani; Raucci, Federica; Letek, Michal; Bauer, Martina; D'Acquisto, Fulvio (Frontiers in Immunology, 2018)
The infiltration of Th17 cells in tissues and organs during the development of many autoimmune diseases is considered a key step towards the establishment of chronic inflammation. Indeed, the localized and prolonged release of IL-17 in specific tissues has been associated with an increased severity of the inflammatory response that remains sustained over time. The cellular and molecular mechanisms behind these effects are far from being clear. In this study we investigated the effects of two repetitive administration of recombinant IL-17 into the murine air pouch to simulate a scenario where IL-17 is released over time in a pre-inflamed tissue. Consistent with our previous observations, mice receiving a single dose (primary) of IL-17 showed a transitory influx of neutrophils into the air pouch that peaked at 24 hours and declined at 48 hours. Conversely, mice receiving a double dose of the cytokine – one at time 0 and the second after 24hr – showed a more dramatic inflammatory response with almost 2-fold increase in the number of infiltrated leukocytes and significant higher levels of TNF- and IL-6 in the inflammatory fluids. Further analysis of the exacerbated inflammatory response of double-injected IL-17 mice showed a unique cellular and biochemical profile with inflammatory monocytes as the second main population emigrating to the pouch and IL-16 and TREM-1 as the most upregulated cytokines found in the inflammatory fluids. Most interestingly, mice receiving a double injection of IL-1β did not show any change in the cellular or biochemical inflammatory response compared to those receiving a primary injection or just vehicle. Collectively these results shed some light on the function of IL-17 as pro-inflammatory cytokine and provide possible novel ways to target therapeutically the pathogenic effects of IL-17 in autoimmune conditions.